Database schema invariant to subject domains and its distinctive features - Yesin, V.I. (Radiotekhnika, 2018)
The desire to avoid unnecessary costs inherent in the traditional methodology of creating relational databases, not only at the stages of conceptual and logical design, but also at the stage of physical design, has actualized the task of developing a database schema that is invariant to subject domains. The main developed and distinguishing elements of this scheme are as follows: composition, structure of the basic relations; implementation of integrity constraints; means ensuring the database security.